The Relationship between Acceptance and Adherence to ARV among Elderly persons. A Case Study of Kakiri Health Centre. - Buthamira, Braos Elisha M. (Student’s Journal of Health Research Africa, 2022)
Background World Health Organization (WHO) recommendations using age 50 and older are defined for older persons. Medication adherence is so critical to the success of HIV management and its comorbidities. However being on new regimens may increase the effectiveness despite suboptimal adherence, past work may demonstrate that in the majority of regimens, patients need to adhere to HIV treatment at the perfect rates possible to counter disease progression, multidrug resistances, and immunologic failures. Methodology A case study design with both qualitative and quantitative research approaches is used in Kakiri Health Centre which is found in the Central part of Uganda-Kakiri Town Council. The study was conducted among elderly individuals who have lived with HIV and on ARV. Results The majority 140(73%) of the respondents were between 65-74 years, whereas 52(27%) were 75-84 years. This implies that most of the adults in the ART clinic were 65-74 years. There is a positive significant relationship between acceptance and adherence to ARV (r = 0.369, p = 0.001). The findings suggest that people with acceptance tend to have good adherence to ARV. Conclusion In light of the study findings, the study concludes that there was high acceptance and adherence to ARV among elderly persons living with HIV in the case of Kakiri Health Centre HIV Clinic. Recommendation In line with the first objective, the study recommends that there should be achievable psychological strategies like psycho-education exposed to the psychologists and counselor trainers so that they come up with effective and empirically proven psychological interventions for the families faced with acceptance and adherence to help affected victims in families. This will be helpful in the mitigation of poor adherence and its long-term effect on persons who have been affected by the situation.